2018
DOI: 10.1186/s12943-018-0767-3
|View full text |Cite
|
Sign up to set email alerts
|

Novel evidence for a PIWI-interacting RNA (piRNA) as an oncogenic mediator of disease progression, and a potential prognostic biomarker in colorectal cancer

Abstract: BackgroundEmerging evidence suggests that PIWI-interacting RNAs (piRNAs) may be important epigenetic regulators of gene expression in human cancers; however, their functional and clinical significance in colorectal cancer (CRC) remains unknown.MethodsWe performed piRNA expression profiling in paired cancer and normal tissues through small RNA-sequencing. The clinical significance of candidate piRNAs was investigated, and independently validated in 771 CRC patients from three independent cohorts. The biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
123
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(139 citation statements)
references
References 43 publications
4
123
0
Order By: Relevance
“…In recent years, small non‐coding RNAs, including miRNAs, siRNAs, and piRNAs has garnered the attention of the researchers in the field of gene regulation and epigenetics . Recent studies have shown that piRNAs, a newly discovered class of ncRNAs are differentially expressed in cancers and regulate several key biological processes revealing their tumorigenic potential (tumor suppressors or oncogenes) . Hence, this class of ncRNAs has the potential to be used as diagnostic and prognostic markers as well as therapeutic interventions for different types of human cancers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, small non‐coding RNAs, including miRNAs, siRNAs, and piRNAs has garnered the attention of the researchers in the field of gene regulation and epigenetics . Recent studies have shown that piRNAs, a newly discovered class of ncRNAs are differentially expressed in cancers and regulate several key biological processes revealing their tumorigenic potential (tumor suppressors or oncogenes) . Hence, this class of ncRNAs has the potential to be used as diagnostic and prognostic markers as well as therapeutic interventions for different types of human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, our lab has also reported the expression of piRNAs in human brain, and Alzheimer's disease (AD)‐affected brain, epithelial ovarian cancer sub‐types and neuroblastoma . Further, aberrant expression of piRNAs has been documented in cancers such as breast, pancreas, lung, kidney, colorectal, cervical, head, neck, and gastric cancer . However, only a few piRNAs such as piR‐651, piR‐20365, piR‐021285, piR‐932, and piR‐823 have been intensively explored and validated in different cancers to decipher their role in oncogenesis .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the failure of apoptosis leads to cancer cell survival and malignancy [Pileczki et al, 2016]. Numerous studies have shown several piR-NAs are upregulated in cancers and their inhibition leads to induce apoptosis [Weng et al, 2018;Yan et al, 2015;Yao et al, 2016]. Therefore, we assessed the role of piR-39980 in the apoptosis of OS cells by transfecting with its inhibitor.…”
Section: Silencing Of Pir-39980 Induces Apoptosis In Os Cellsmentioning
confidence: 99%
“…Among ncRNAs, Piwi-interacting RNAs (piRNAs) have recently emerged as promising ncR-NAs which are initially reported to maintain genome stability either by post-transcriptional silencing or by histone modification and DNA-methylation of transposons in association with PIWI-proteins [Brennecke et al, 2007;Ku and Lin, 2014;Houwing et al, 2007;Castel and Martienssen, 2013;Watanabe and Lin, 2014]. These are of ß26-36 nucleotides (nts) in length characterised by a 3-terminal 2´-Omethylation and are now reported in somatic and cancer cells regulating differentiation, development, proliferation, apoptosis, invasiveness, angiogenesis, chemo-resistance and so on besides their germline functions [Bahn et al, 2015;Khurana and Theurkauf, 2010;Xiong et al, 2015;Weng et al, 2018;Firmino et al, 2016]. More specifically, only a few piRNAs such as piR-651, piR-20365, piR-021285, piR-932 and piR-823 have been reported to regulate oncogenesis of various cancers such as breast, pancreas, lung, kidney, colorectal, cervical, head, neck and gastric cancer [Zhang et al, 2013;Li et al, 2016;Cordeiro et al, 2016;Fu et al, 2015;Yin et al, 2017].…”
Section: Introductionmentioning
confidence: 99%